Aspects of the physiology of crustacea - Lockwood, A. P. M. (W. H. Freeman and Company, 1967)
This book includes many parts: osmotic and ionic regulation, moulting, hormones, the blood system, respiration and metabolism, the neurmuscular system, sense organs, feeding and digestion.